Comparative Efficacy and Acceptability of Endoscopic Methods for Rectal Neuroendocrine Neoplasms with Low Malignant Potential: A Network Meta-analysis - Zhang, Shun-Tao; Chen, Qi; Zhang, Yuan-Meng; Li, Qiao-Yu; Gao, Yu-Chen; Meng, Wen-Jun; Qiu, Lie-Wang; Zeng, Bo (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Although endoscopic resection is an effective treatment of rectal neuroendocrine neoplasms (R-NENs) with low malignant potential, there is no consensus on the most recommended endoscopic method. This study aimed to assess the efficacy and acceptability of different endoscopic treatments for R-NENs with low malignant potential. Materials and Methods: We searched databases for studies on treatments of R-NENs using endoscopic resection. These studies comprised techniques such as endoscopic mucosal resection (EMR), endoscopic submucosal dissection (ESD), modified endoscopic mucosal resection (EMRM), modified endoscopic submucosal dissection (ESDM), and transanal endoscopic microsurgery (TEM). The primary outcomes assessed were histological complete resection (HCR). Results: Overall, 38 retrospective studies (3040 R-NENs) were identified. Endoscopic mucosal resection with a cap (EMRC), endoscopic mucosal resection with ligation (EMRL), ESD, ESDM, and TEM demonstrated higher resectability than did EMR in achieving HCR. Endoscopic mucosal resection, EMRC, EMRL, EMRP, EMRD, and EMRU required shorter operation times than did ESD. Endoscopic mucosal resection, EMRC, ESDM, and TEM incurred lower risks than did ESD. Conclusion: Regarding R-NENs ≤20 mm with low malignant potential, ESD could be used as the primary treatment. However, TEM may be more effective if supported by economic conditions and hospital facility. With respect to R-NENs ≤16 mm with low malignant potential, EMRL could be used as the primary treatment. In regard to R-NENs ≤10 mm with low malignant potential, EMRL, EMRC, and ESD could be used as the primary treatment. However, EMRL and EMRC might be better when operational difficulties and economic conditions were considered. Cite this article as: Zhang S, Chen Q, Zhang Y, et al. Comparative efficacy and acceptability of endoscopic methods for rectal neuroendocrine neoplasms with low malignant potential: A network meta-analysis. Turk J Gastroenterol. 2024;35(6):440-452.